Acute‐onset chronic inflammatory demyelinating polyneuropathy: An electrodiagnostic study. Issue 5 (31st August 2015) - Anadani, Mohammad; Katirji, Bashar
ABSTRACT Introduction: Acute‐onset chronic inflammatory demyelinating polyneuropathy (A‐CIDP) is an increasingly recognized CIDP subtype. Differentiating A‐CIDP from Guillain–Barré syndrome (GBS) is challenging but important, because there are different treatment outcomes. Methods: We report 3 patients with A‐CIDP who were initially diagnosed with severe GBS but were later confirmed to have CIDP based on their clinical course and electrodiagnostic (EDx) studies. We also report on the long‐term treatment of these patients and review the literature on EDx studies in this syndrome. Results: Three patients were initially diagnosed with GBS and responded to treatment. However, all 3 had arrest in improvement or deterioration during their rehabilitation phases. EDx studies showed prominent demyelinating changes many months after the initial presentation. All responded very well to immunotherapy. Conclusion: Although several features may suggest the diagnosis of A‐CIDP at initial presentation, close follow‐up of GBS patients during the recovery phase is also needed for accurate diagnosis. EDx studies may distinguish patients with A‐CIDP from GBS patients. Muscle Nerve52: 900–905, 2015